Chemoreactome analysis of the antithrombotic effects of glucosamine sulfate and nonsteroidal anti-inflammatory drugs - O. A. Gromova; I. Yu. Torshin; A. M. Lila; A. V. Naumov; K. V. Rudakov (Современная ревматология)
Nonsteroidal anti-inflammatory drugs (NSAIDs) are among the most effective medications in modern pharmacotherapy. At the same time, it has been established that NSAIDs can cause cardiovascular diseases. Glucosamine sulfate (GS) is used in the therapy of osteoarthritis and, according to experimental data; it can exert an antithrombotic effect. This paper evaluates the antithrombotic effects of GS and a number of NSAIDs (such as, acetylsalicylic acid (ASA), dexketoprofen, diclofenac, and meloxicam) through chemoreactome analysis. It has been found that the antithrombotic effects of GS can be on average only 1.5—3 times weaker than those of the NSAIDs studied. The findings may suggest that GS can enhance the antithrombotic effect of ASA, in particular in the presence of cardiovascular disease in patients with osteoarthritis.